1999
DOI: 10.2337/diacare.22.7.1191
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance and classic risk factors in type 2 diabetic patients with different subtypes of ischemic stroke.

Abstract: Patients with LAC, ATI, and LAA were significantly older and were more likely to be hypertensive than patients with NOR. Significantly higher insulin resistance was observed in patients with LAC, ATI, and LAA than in patients with NOR (KITT 2.21 +/- 0.17, 2.10 +/- 0.17, 2.19 +/- 0.25, and 3.25 +/- 0.21% per min, respectively, P < 0.001). Adjustment for age, sex, BMI, and duration of diabetes did not influence this result. Multiple logistical regression analysis showed that insulin resistance was an independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
4

Year Published

2000
2000
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 0 publications
0
28
0
4
Order By: Relevance
“…23 The risk factors for stroke previously reported were diabetic history, SBP, 24 and insulin resistance. 25 In a report on poststroke patients, 26 hypertension and DM were closely related to multiple SCIs. We recently reported that insulin resistance-related hemostatic abnormality is associated with multiple SCIs in hypertensive patients.…”
Section: Impact Of Coexisting Dm and Hypertensionmentioning
confidence: 99%
“…23 The risk factors for stroke previously reported were diabetic history, SBP, 24 and insulin resistance. 25 In a report on poststroke patients, 26 hypertension and DM were closely related to multiple SCIs. We recently reported that insulin resistance-related hemostatic abnormality is associated with multiple SCIs in hypertensive patients.…”
Section: Impact Of Coexisting Dm and Hypertensionmentioning
confidence: 99%
“…22 Although insulin resistance seems to be related to hypertension and dyslipidemia, 23,24 our study indicated that age, systolic and diastolic blood pressure, and serum lipids were not different across the groups of various glucose levels. Matsumoto et al 25 evaluated the correlation between insulin resistance and classic risk factors in type 2 diabetes patients with various subtypes of ischemic stroke by using the K index of the insulin tolerance test. In their results, hyperinsulinemia as a surrogate marker for insulin resistance was a risk factor for ATI.…”
Section: Discussionmentioning
confidence: 99%
“…The adverse effects of IR on the peripheral and coronary circulations have been studied extensively, and vascular dysfunction emerges as a major factor in the development of hypertension and coronary artery disease (5)(6)(7)(8)(9)(10). In sharp contrast, changes in regulatory mechanisms of the cerebral circulation are virtually unexplored, despite the fact that IR, as well as type 2 diabetes, increases the prevalence of cerebrovascular events, and IR patients with stroke are subject to more severe progression, slower recovery, and higher mortality (11)(12)(13)(14). In addition, obesity and IR in older people are risk factors for dementia, particularly Alzheimer's disease (15)(16)(17), which might be related to cerebrovascular dysfunction and chronic hypoperfusion of the brain (18,19).…”
mentioning
confidence: 99%